Study on influence of ambient temperature on biaxial stress and strength of flexible inflatable wing film - Longbin Liu; Fan Hu; Zhenyu Jiang; Ting Liu; Yonggang Xu (Results in Physics, 2019)
With advantages of small folding volume, light weight, simple structure, low cost and so on, the flexible inflatable wing has attracted many researchers' attention. However, the change of ambient temperature has a significant influence on the bearing stress of the flexible inflatable wing. Here the typical flat inflatable wing was taken as the object, and the biaxial stress analysis and the Mises stress of the influence of the ambient temperature of the inflatable wing were constructed adopting the mechanical theory and balance principle. And the finite element simulation calculation under different ambient temperature was also performed with the theoretical model. It is found that the biaxial stress and strength of the flexible wing film are closely related to the ambient temperature, and the temperature changings will cause the wing stress to change the Mises stress distribution law of the upper and lower airfoil surfaces, and the wing skin is a two-phase plane stress state. Moreover, with the increase of the ambient temperature, the changes of the Mises stress of the wing root, middle and wingtips of the whole airfoil are inconsistent, but the overall warping deformation is improved, which provides a theoretical reference for the structural optimization design and strength analysis of the flexible inflatable wing. Keywords: Biaxial tension, Flexible inflatable wing, Strength, Stress, Thin film theory